Szybkość biegu 16-letniej młodzieży w aspekcie uwarunkowań somatycznych oraz motorycznych = Speed of running of 16-year-old adolescents in the aspect of somatic-motor conditionings - Marciniak, Anna; Lewandowski, Jacek (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is an attempt to determine the differences in the conditionings of locomotion speed between the group of girls and the group of boys, and to show the dependency between manifestations of locomotion speed and somatic and motor parameters in both groups.
Keywords: locomotion speed; strength; somatic parameters; prędkość lokomocyjna; siła; parametry somatyczne